Implementasi Pembelajaran Sains Anak Usia Dini Melalui Pendekatan Guided Inquiry - Harlistyarintica, Yora; Muryani, Arlis (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Guided inquiry approach in early childhood science learning can provide opportunities for children to conduct investigations and motivate children to gain new knowledge that is more meaningful according to their age. This qualitative descriptive study describes the application of the guided inquiry approach in early childhood science learning. Data collection techniques used documentation studies and semi-structured interviews. A total of ten teachers from five kindergartens in Yogyakarta City became informants in this study. The results of the survey prove that applying science learning with a guided inquiry approach is very effective in stimulating basic science process skills in early childhood and makes it easier for children to understand science concepts with teacher guidance in a fun way.